Atmospheric boundary layers nature, theory, and application to environmental modelling and security - NATO Advanced Research Workshop "Atmospheric Boundary Layers: Modelling and Applications to Environmental Security" (Springer)
Most of practically-used turbulence closure models are based on the concept of downgra- ent transport. Accordingly the models express turbulent uxes of momentum and scalars as products of the mean gradient of the transported property and the corresponding turbulent transport coef cient (eddy viscosity, K , heat conductivity, K , or diffusivity, K ). Fol- M H D lowing Kolmogorov (1941), turbulent transport coef cients are taken to be proportional to the turbulent velocity scale, u , and length scale, l : T T K ? K ? K ? u l . (1) M H D T T 2 Usually u is identi ed with the turbulent kinetic energy (TKE) per unit mass, E ,and K T is calculated from the TKE budget equation using the Kolmogorov closure for the TKE dissipation rate: ? ? E /t , (2) K K T where t ? l /u is the turbulent dissipation time scale. This approach is justi ed when it T T T is applied to neutral stability ows, where l can be taken to be proportional to the distance T from the nearest wall. However, this method encounters dif culties in strati ed ows (both stable and uns- ble). The turbulent Prandtl number Pr = K /K exhibits essential dependence on the T M H strati cation and cannot be considered as constant. Atmospheric boundary layers: nature, theory and applications to environmental modelling and security -- Some modern features of boundary-layer meteorology: a birthday tribute for Sergej Zilitinkevich -- Energy- and flux-budget (EFB) turbulence closure model for stably stratified flows. Part I: steady-state, homogeneous regimes -- Similarity theory and calculation of turbulent fluxes at the surface for the stably stratified atmospheric boundary layer -- Application of a large-eddy simulation database to optimisation of first-order closures for neutral and stably stratified boundary layers -- The effect of mountainous topography on moisture exchange between the “surface” and the free atmosphere -- The influence of nonstationarity on the turbulent flux–gradient relationship for stable stratification -- Chemical perturbations in the planetary boundary layer and their relevance for chemistry transport modelling -- Theoretical considerations of meandering winds in simplified conditions -- Aerodynamic roughness of the sea surface at high winds -- Modelling dust distributions in the atmospheric boundary layer on Mars -- On the turbulent Prandtl number in the stable atmospheric boundary layer -- Micrometeorological observations of a microburst in southern Finland -- Role of land-surface temperature feedback on model performance for the stable boundary layer -- Katabatic flow with Coriolis effect and gradually varying eddy diffusivity -- Parameterisation of the planetary boundary layer for diagnostic wind models.